A Rare Case of Bilateral Achilles Tendon Xanthomas in a Teenager, Successfully Treated with Tendon Sparing Technique - G. A. P. K. Appuhamy; B. M. Munasinghe; L. M. Soysa; D. Nelson; P. G. P. Ranmini; W. T. Pavithra; W. M. Sajini; C. D. N. Anthony (Case Reports in Orthopedics)
Background. Xanthoma of the Achilles tendon, even though being benign, is a surgically challenging orthopaedic condition. Causality is believed to be due to a pathological error in the metabolism of low-density lipoprotein and their resultant accumulation, as foam cells within the tendon. Tendon xanthomas are often found to accompany heterozygous familial hypercholesterolemia. Case Presentation. A 19-year-old girl presented to our institution (a District General Hospital), with soft tissue lumps over posterior aspect of the ankle on both sides for several years. She had noticed a rapid increase in size in recent 3 months and sought medical advice. During investigation, she was diagnosed having bilateral Achilles tendon xanthomas clinically, confirmed by ultrasound scan and magnetic resonance imaging, and familial hypercholesterolemia concomitantly. The former was managed with intralesion subtotal resection where the histology further confirmed the diagnosis. The patient was commenced on statins and followed up while assessing the functional outcome and recurrences up to 2 years, with favourable results. Conclusion. Subtotal resection of Achilles tendon xanthoma (tendon sparingly) offers cosmetically and functionally acceptable outcomes, with faster recovery and no recurrences over 2 years.